2021
DOI: 10.1002/ajmg.a.62410
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical phenotype of RASopathies in 38 Turkish patients, including the rare LZTR1, RAF1, RIT1 variants, and large deletion in NF1

Abstract: RASopathies are a group of disorders caused by pathogenic variants in the genes encoding Ras/mitogen-activated protein kinase pathway and share overlapping clinical and molecular features. This study is aimed to describe the clinical and molecular features of 38 patients with RASopathies. Sanger or targeted next-generation sequencing of related genes and multiplex ligation-dependent-probe amplification analysis for NF1 were performed. The pathogenic variant detection rate was 94.4%.While PTPN11 was responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
2
2
Order By: Relevance
“…Therefore, an increase in the number of subjects that were examined appears to have provided more accurate information regarding the genetic background of NS in Japanese patients, as the global frequency of PTPN11 variants in NS was reported to be approximately 50% ( 15 ). In the present study, the detection rate of RIT1 variants was 9%, and this was higher than that reported in Europe and Brazil (5–6%) ( 33 , 34 , 35 ). In Eastern Asia, the detection rates of RIT1 are 7.5% in Japan ( 27 ) and 6.8% in China ( 36 ).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Therefore, an increase in the number of subjects that were examined appears to have provided more accurate information regarding the genetic background of NS in Japanese patients, as the global frequency of PTPN11 variants in NS was reported to be approximately 50% ( 15 ). In the present study, the detection rate of RIT1 variants was 9%, and this was higher than that reported in Europe and Brazil (5–6%) ( 33 , 34 , 35 ). In Eastern Asia, the detection rates of RIT1 are 7.5% in Japan ( 27 ) and 6.8% in China ( 36 ).…”
Section: Discussioncontrasting
confidence: 83%
“…We investigated the genetic background of patients clinically diagnosed with NS and determined that the percentage of subjects harboring pathogenic variants was 86%. The detection rates of pathogenic variants vary among studies and range from 50% to more than 90% in patients with NS or RASopathies ( 3 , 33 , 34 , 35 , 36 ). A recent review by Tartaglia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Most RASopathy genes such as PTPN11 , BRAF , and NF1 reported to be associated with 50% Noonan syndrome, 75% Cardio-facio-cutaneous syndrome, and > 95% neurofibromatosis type 1 cases, respectively (Abdel-Aziz et al 2021 ; Athota et al 2020 ; Başaran 2021 ; Pierpont et al 2014 ), and yielded expected detection rates as reported in the literature. Unexpected finding was observed in SOS1 and RAF1 genes which are both reported to be associated with 10–20% of Noonan syndrome cases (Alkaya et al 2021 ), and were observed at lower detection rate of 6% each in the current study. However, each gene had two variants identified which is relatively low to make significant comparisons.…”
Section: Discussioncontrasting
confidence: 49%
“…Approximately 75% of the pathogenic RAF1 mutations identified to date are located in the N-terminal kinase functional domain of the RAF1 protein, with 15% affecting the phosphorylation of the C-terminal residues ( Tartaglia et al, 2011 ). Recent studies on the phenotype of RASopathies have reported joint dislocations and other skeletal deformities in patients with mutations in the Ras/ERK pathway ( Tartaglia et al, 2011 ; Uludağ Alkaya et al, 2021 ). Patients with RASopathies exhibit phenotypes of limb malformations, and evidence from embryonic development suggests that RAF1 may have a significant impact on limb development.…”
Section: Introductionmentioning
confidence: 99%